2008
DOI: 10.1007/s11442-008-0142-1
|View full text |Cite
|
Sign up to set email alerts
|

Cloudiness variations over the Qinghai-Tibet Plateau during 1971–2004

Abstract: With Empirical Orthogonal Function (EOF) and trend analysis method adopted, the spatio-temporal variation of total cloud amount is analyzed for 75 stations on the Qinghai-Tibet Plateau during the period 1971-2004. Analysis indicates that the total cloud amount decreases from the southeast to the northwest of the plateau, and that the annual and seasonal variations in total cloud amount both show an apparent declining tendency over the past decades. Correlation analysis demonstrates that the total cloud amount … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 26 publications
4
34
0
Order By: Relevance
“…It's clearly seen that negative high value of CRF mainly distributes in the southeast Tibetan Plateau (Szechwan Basin and Guizhou), Hunan, Jiangxi and southeast coast; beyond north of 40 degree the CRF values are generally small; strong cloud forcing with negative high CRF value presents in cloudy area in Bangladesh over southeast Tibetan Plateau, while weak cloud forcing with negative low CRF value appears on the Qaidam Basin over the north plateau. These regional characteristics of CRF are highly consistent with the distribution of total cloud amount in China and Tibetan Plateau [12].…”
Section: A the Spatial Distribution Of Interannual Crfsupporting
confidence: 75%
“…It's clearly seen that negative high value of CRF mainly distributes in the southeast Tibetan Plateau (Szechwan Basin and Guizhou), Hunan, Jiangxi and southeast coast; beyond north of 40 degree the CRF values are generally small; strong cloud forcing with negative high CRF value presents in cloudy area in Bangladesh over southeast Tibetan Plateau, while weak cloud forcing with negative low CRF value appears on the Qaidam Basin over the north plateau. These regional characteristics of CRF are highly consistent with the distribution of total cloud amount in China and Tibetan Plateau [12].…”
Section: A the Spatial Distribution Of Interannual Crfsupporting
confidence: 75%
“…During 1971–2004, the annual mean total cloud cover on the TP ranges from over than 64% in the southeast to less than 44% in the northern and southwestern parts [ Zhang et al , ]. A significant decreasing trend in total cloud cover has been observed on the TP since the 1950s [ Kaiser , ; Niu et al , ; Duan and Wu , ; Zhang et al , ; You et al , ; Yang et al , ; Yang et al , ; You et al , ; You et al , ]. The total cloud cover over the TP shows a decreasing trend of −0.49% decade −1 during 1961–2013 [ You et al , ], which is shown in Figure a.…”
Section: Changes In Other Climate Variablesmentioning
confidence: 99%
“…Most stations on the TP show decreasing trends in total cloud cover [ Kaiser , ; Niu et al , ; Zhang et al , ; You et al , ]. About 65% of the stations show significant decreasing trends with the most significant decrease in the central TP [ You et al , ].…”
Section: Changes In Other Climate Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…These trends in dimming and brightening have been attributed to atmospheric aerosols but for the Tibetan Plateau region the observations are much more limited and our understanding of these trends and their causes less clear. Duan and Wu (2006) reported changes in cloud amount over the Tibetan Plateau [also identified by Zhang et al (2008) and Yang et al (2012)] and suggested that these changes (i.e., daytime decrease, nighttime increase) played a role in the temperature increase in the region, through their radiative impact. Ye et al (2009), for example, found a strong correlation between surface downward shortwave fluxes and the diurnal temperature range.…”
Section: Introductionmentioning
confidence: 95%